Chelovek i zakon . Chelovek i zakon . People and the Law . Человек и закон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on the seizure of schoolchildren as hostages in Rostov-on-Don on December 23, 1993, and discussion of legal protection for Russian business. Contributors: Karpov, Aleksandr (Anchor) Программа рассказывает о захвате в заложники школьников в Ростове-на-Дону 23 декабря 1993 года и о проблеме правовой защиты российского бизнеса. Создатели: Карпов, Александр (Ведущий/Ведущая)